ANALYSIS OF CONTEXTUAL PROBLEM-SOLVING INSTRUCTION IN THE CONSTRUCTION OF ELEMENTARY STUDENTS’ MATHEMATICAL CONCEPTUAL UNDERSTANDING - Yuhanita Ulzana; Mohamad Syahri; Mohammad Syaifuddin (JURNAL EDUSCIENCE, 2026)
Purpose – This study aims to analyze contextual problem-solving instruction as a pedagogical space for constructing elementary students' mathematical conceptual reasoning in whole-number learning. The study focuses on how authentic problems, everyday-life contexts, and instructional interaction facilitate students' construction of conceptual meaning and their explanation of the rationale for using arithmetic operations.Methodology – This study employed a field-based qualitative case study approach. Researchers collected data through classroom observations, interviews with the school principal, teacher, and selected students, document analysis, and pretest–posttest measures as supporting descriptive data. Data were analyzed through data reduction, data display, and conclusion drawing, while trustworthiness was ensured through source, technique, and time triangulation.Findings – The findings show that contextual problem-solving instruction created a learning space that enabled students to actively, reflectively, and meaningfully construct mathematical conceptual reasoning. Through simple buying-and-selling contexts, the use of play money, group discussion, and reflection, students were able to identify information, select solution strategies, explain the rationale for using addition and subtraction, and relate whole-number concepts to real-life situations.Contribution – This study confirms that contextual problem-solving instruction should be understood not merely as a strategy for improving learning outcomes, but as a pedagogical space that facilitates the construction of students’ mathematical conceptual reasoning through authentic experience, social interaction, and reflection on thinking processes.